ANALISIS PROSES PEMBELAJARAN DAN INTEGRASI PENGETAHUAN COVID 19 DALAM SATUAN PENDIDIKAN - Aja Salmiati; Bazelia Izasatifa; Nurmalahayati Nurmalahayati (Postgraduate, University of Mataram, 2022)
The research aims to find out information about the learning process and the integration of COVID-19 knowledge in education units in Aceh Barat Daya. Based on the results obtained showed that the learning systems that are generally applied during the pandemic are blended learning with a percentage of 42.9%, offline learning 28.6% and online learning 28.6%. Face-to-face learning is carried out through the division of study groups, while online learning is carried out by utilizing learning applications. The education unit at Aceh Barat Daya has tried to implement the policies of the central government and local governments while carrying out learning during the pandemic. This can be observed from the efforts of the school in implementing health protocols while studying during the pandemic. In addition, the school also provides free health facilities and infrastructure and free internet quota to support the learning process. Education related to the dangers of coronavirus is carried out by the school in various ways, both by socializing the dangers of COVID-19 in the school and by giving direction for teachers to exemplify COVID-19 prevention behavior. Education is also carried out by making disinfectants independently and sharing information about covid-19 through social media